Al-Qaradawi Dan Orientasi Pemikiran Hukum Islam untuk Menjawab Tuntutan Perubahan Sosial - Badri Khaeruman (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2016)
The appearance of Yusuf al-Qaradawi, who is famous for his fatwas, seems to respond to the need of reform in Islamic legal thought in order for it to be more relevant. His works, such as Al-Ijtihad al-Mu’asir baina al-Indhibat wa al-Infirat, Al-Halal wa al-Haram fi al-Islam dan Min Hadyi al-Islam Fatawa Mu’ashirah, shows his contribution to the development of Islamic legal thought today. Al-Qaradawi says that the need for such a reform due to changes in almost all aspects of human life, where arise new issues that the legal status of which can not be found directly both in the scriptural texts and fatwas of religious scholars in the past. To reply the need of legal reform, al-Qaradawi propossed two methods, namly intiqai (tarjih of the existing fatwas) dan inshai (method to find out solutions for new issues that emerged in contemporary situation), with some requirements. In dealing with contemporary issues, his orientation of developing Islamic legal thought tends to be moderate between the two extreme ones, ifrat (excessive) dan tafrit (oversimplipying). He holds the principle of  ”taysir (to provide comvenience)” and of ”integration between legal views that are salafiah (scriptural) and renewal”, which considers the social change not as a threat to the alienation of Islamic legal tought in the mids of public lives, but as a grace. In his legal perpective, the progress of science and technology that drive the various changes is synonymous with ease.